2022
DOI: 10.1186/s12882-022-02677-y
|View full text |Cite
|
Sign up to set email alerts
|

Using dipstick urinalysis to predict development of acute kidney injury in patients with COVID-19

Abstract: Background Acute kidney injury (AKI) is a common complication in patients hospitalized with COVID-19 and may require renal replacement therapy (RRT). Dipstick urinalysis is frequently obtained, but data regarding the prognostic value of hematuria and proteinuria for kidney outcomes is scarce. Methods Patients with positive severe acute respiratory syndrome-coronavirus 2 (SARS-CoV2) PCR, who had a urinalysis obtained on admission to one of 20 hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…This may be attributable to many factors, including the time point of testing and different proportion of severe cases in studied countries, and/or different scales of patient sampling. Furthermore, several publications reported the important role of urine tests in evaluating the severity, occurrence of AKI, and clinical course of COVID-19 patients, supporting the utility of urine as an informative biospecimen [29][30][31].…”
Section: Discussionmentioning
confidence: 91%
“…This may be attributable to many factors, including the time point of testing and different proportion of severe cases in studied countries, and/or different scales of patient sampling. Furthermore, several publications reported the important role of urine tests in evaluating the severity, occurrence of AKI, and clinical course of COVID-19 patients, supporting the utility of urine as an informative biospecimen [29][30][31].…”
Section: Discussionmentioning
confidence: 91%
“…Proteinuria and hematuria are not as critical clinically as AKI, but their influence on COVID-19 prognosis cannot be overlooked. Proteinuria and hematuria can be used as independent predictors of COVID-19 severity [ 26 , 27 ]. Our study demonstrated that proteinuria was significantly associated with Omicron variant infection.…”
Section: Discussionmentioning
confidence: 99%
“…Naomi et al ( 32 ) reported the application of serum biomarkers (SB), including serum NGAL and serum creatinine, for the prediction of AKI in 52 COVID-19 patients, with AUCs of 0.81 and 0.87, respectively. A prediction model for AKI based on proteinuria and hematuria yielded an AUC of 0.64 (95% CI: 0.62–0.67) in a large cohort study containing 5,980 COVID-19 patients; moreover, the predictive capability of the model was improved when creatinine and the presence of CKD were incorporated ( 33 ). In addition, studies have validated the predictive value of other indicators, such as D-dimer and albumin/creatinine ratio, for AKI in hospitalized COVID-19 patients ( 34 ).…”
Section: Discussionmentioning
confidence: 99%